Assemblages of Health Deleuze's Empiricism and the Ethology of Life - Duff, Cameron; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
This book presents a review of Deleuze$1 (Bs key methods and concepts in the course of exploring how these methods may be applied in contemporary studies of health and illness. Taken from a Deleuzian perspective, health and wellbeing will be characterized as a discontinuous process of affective and relational transitions. The book argues that health, conceived in terms of the quality of life, is advanced or facilitated in the provision of new affective sensitivities and new relational capacities. Following an assessment of Deleuze$1 (Bs key ideas, the book will offer a series of case studies designed to illustrate how Deleuze$1 (Bs ideas can be applied to select health problems. This analysis draws out the specific advantages of a Deleuzian approach to public health research, establishing grounds for more widespread engagement with Deleuze$1 (Bs ideas across the health and social sciences.s
Chapter 1. Introduction: Assemblages of Health -- Chapter 2. The Concrete Richness of the Sensible -- Chapter 3. Health, Ethology, Life -- Chapter 4. The Assemblage in Recovery (Mental Health) -- Chapter 5. Assemblages of Drugs, Spaces and Bodies -- Chapter 6. The Ethics of an Assemblage of Health -- Chapter 7. Conclusion: A Line of Becoming Well.
Keywords: Social sciences; Philosophy and social sciences; Public health; Medical research; Quality of life; Social Sciences; Quality of Life Research; Public Health; Philosophy of the Social Sciences; Electronic books